The Effect of Internal Control and Good Corporate Governance on Company Performance at PT PAL Indonesia - Aulia, Nisa Fitri; Bayangkara, Ida Bagus Ketut (Peneliti.net, 2024)
The aim of this study was to evaluate the influence of internal control and good corporate governance on the performance of PT PAL Indonesia. The research utilized a sample of 50 respondents for data collection, and the analysis involved statistical methods such as descriptive testing, data quality evaluation, classical assumption testing, and hypothesis testing. The results of the data analysis indicate that internal control has a partially positive and significant impact on company performance. Additionally, the study reveals that good corporate governance has a positive and significant effect on company performance. When both variables, internal control and corporate governance, are examined simultaneously, they exhibit a positive and significant impact on company performance. Consequently, these findings constitute a noteworthy contribution within the realm of corporate governance, underscoring the critical importance of implementing internal control and adopting good corporate governance as pivotal factors in enhancing the performance of PT PAL Indonesia. The practical implications derived from these study results can serve as a basis for companies to optimize their strategies related to internal control and corporate governance, thereby achieving their performance objectives more effectively.